2013
DOI: 10.1111/bij.12153
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of postzygotic reproductive isolation in galliform birds: analysis of first and second hybrid generations and backcrosses

Abstract: The process of speciation is a crucial aspect of evolutionary biology. In this study, we analysed the patterns of evolution of postzygotic reproductive isolation in Galliformes using information on hybridization and genetic distance among species. Four main patterns arose: (1) hybrid inviability and sterility in F1 hybrids increase as species diverge; (2) the presence of geographical overlap does not affect the evolution of postzygotic isolation; (3) the galliforms follow Haldane's rule; (4) hybrid inviability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 61 publications
(91 reference statements)
3
30
0
Order By: Relevance
“…Second, the evolution of reproductive isolation is protracted in birds relative to other taxa (Prager and Wilson 1975;Fitzpatrick 2004;Price 2008). Astoundingly, fully fertile hybrids have been documented from bird species that have diverged for up to 10 million years (Tubaro and Lijtmaer 2002;Lijtmaer et al 2003;Price 2008;Arrieta et al 2013). In many other taxa, studies of gene expression have pointed to frequent misexpression in F1 hybrids (Landry et al 2005;McManus et al 2010;Malone and Michalak 2008;Renaut et al 2009;Bell et al 2013;Coolon et al 2014).…”
Section: Dobzhansky-mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the evolution of reproductive isolation is protracted in birds relative to other taxa (Prager and Wilson 1975;Fitzpatrick 2004;Price 2008). Astoundingly, fully fertile hybrids have been documented from bird species that have diverged for up to 10 million years (Tubaro and Lijtmaer 2002;Lijtmaer et al 2003;Price 2008;Arrieta et al 2013). In many other taxa, studies of gene expression have pointed to frequent misexpression in F1 hybrids (Landry et al 2005;McManus et al 2010;Malone and Michalak 2008;Renaut et al 2009;Bell et al 2013;Coolon et al 2014).…”
Section: Dobzhansky-mentioning
confidence: 99%
“…Although there is extensive information about fertility and viability loss in hybrid birds (Tubaro and Lijtmaer 2002;Lijtmaer et al 2003;Price 2008;Arrieta et al 2013), to date there have been no studies of regulatory divergence in bird species and their hybrids. While zebra finches (Taeniopygia guttata) are an established model system for the neurobiology of song learning (Clayton et al 2009), they also have great potential for mechanistic studies of speciation.…”
Section: Dobzhansky-mentioning
confidence: 99%
“…In birds, where sex is determined by a ZZ/ZW system, females are the heterogametic sex and hybrid females are thus expected to show greater fitness reductions compared to male hybrids. This expectation has been confirmed for birds in general (Price and Bouvier, 2002), but also for specific bird groups, including ducks (Tubaro and Lijtmaer, 2002), galliform birds (Arrieta et al, 2013), and pigeons and doves (Lijtmaer et al, 2003). Consequently, introgression of maternally inherited loci, such as mitochondrial and W-linked loci, will be impaired by unfit (e.g., sterile) females.…”
Section: Comparison Of Genomic Classesmentioning
confidence: 76%
“…Such analyses provide insights, not only into the fertility of hybrids, but also into the fertility and viability of backcrosses. For instance, Arrieta et al (2013) showed that hybrid inviability was higher in F 2 compared to F 1 hybrids in galliform birds, indicating that interspecific gene flow may be hampered due to inviable F 2 hybrids. For geese, the fertility of male birds at high genetic distances suggests the possibility of interspecific gene flow between distantly related species (e.g., Greylag Goose and Canada Goose), but if consequent backcrosses are sterile or not viable, then the possibility of interspecific gene flow is greatly reduced.…”
Section: Fertility Of Goose Hybridsmentioning
confidence: 99%
See 1 more Smart Citation